Synthesis, radiolabeling, and evaluation of a 68Ga-labeled tyrosine kinase inhibitor for detecting EGFRT790M mutations in vivo - Xie, Jiajun; Xu, Weiguo; Deng, Hui; Wu, Xiaoai; Zhu, Jing (Frontiers in Bioengineering and Biotechnology, 2026)
Radiolabeled tyrosine kinase inhibitors (TKIs) have been used in clinics for the detection of epidermal growth factor receptor (EGFR) mutations in non-small-cell lung cancer (NSCLC) patients by positron emission tomography (PET), and the potential responder for TKI targeted therapy can be selected and benefited in subsequent TKI-based anti-tumor treatment. However, as activated T790M resistance mutation is often observed in NSCLC patients underwent EGFR TKI based therapies, the detection of EGFR mutation status is of great importance to evaluate therapeutic efficacy and prolongs overall survival with these patients. In addition, no radiotracer has been reported with the ability to detect EGFRT790M mutation in vivo at present. Based on the chemical structure of Rociletinib, a novel radiolabeled PET tracer (68Ga-1) was developed with potent binding affinity in vitro (with IC50 value of 9.21 nM). In addition, 68Ga-1 also showed promising properties in detection EGFRT790M mutation in the subsequent in vitro and in vivo evaluations. Herein we report the synthesis, radiolabeling, and preclinical evaluation of 68Ga-1 for detecting EGFRT790M mutation, and our result indicated that Rociletinib may be regarded as a lead compound to develop a selective EGFRT790M PET tracer with further modification and optimizations.